Influence of cyclodextrins on the gelation behavior of κ-carrageenan/konjac glucomannan composite gel. (November 2021) - Yuan, Chao; Zou, Yiyuan; Cui, Bo; Fang, Yishan; Lu, Lu; Xu, Dongyan
Abstract: The effects of cyclodextrins (CDs) on the gelation behavior of κ-carrageenan/konjac glucomannan (KC/KGM) composite gel were evaluated. The steady shear rheology result showed that the incorporation of CDs reduced the apparent viscosity, yield stress ( τ 0 ) and consistency coefficient ( K ) of KC/KGM composite sol, the shear thinning of the sol was more pronounced. Methyl-β-CD (M-β-CD) exerted the greatest effect. The frequency sweep result showed that CDs enhanced the storage modulus of the composite gel and promoted the formation of more flexible gel structures. The improvement of M-β-CD was more significant than other CDs. Confocal laser scanning microscope images showed that a continuous gel structure formed after the incorporation of α-CD, β-CD or M-β-CD. While the composite gel containing γ-CD or HP-β-CD showed an uneven and discontinuous structure. More hydrogen bond interaction in the gel system formed after the addition of CDs. The presence of CDs strongly contributed to improve the degradation temperature of KC/KGM composite gel and thermal stability. Graphical abstract: Image 1 Highlights: The addition of CDs promoted the dispersion of polysaccharides molecules. The molecular properties of CDs influenced the structure of composite gel. CDs enhanced the intermolecular interaction between the polysaccharide molecules.